Biomechanics and Clinical Application of Translaminar Screws Fixation in Spine: A Review of the Literature. Issue 2 (April 2019) - Chan, Jimmy J.; Shepard, Nicholas; Cho, Woojin
Study Design: Broad narrative review. Objectives: Translaminar screw (TLS) fixation was first described as a salvage technique for fixation of the axial spine. Better understanding of the spine anatomy allows for advancement in surgical techniques and expansion of TLS indications. The goal of this review is to discuss the anatomic feasibility of the TLS fixation in different region of the spine. Methods: A review of the current literatures on the principles, biomechanics, and clinical application of the translaminar screw technique in the axial, subaxial, and thoracolumbar spine. Results: Anatomic feasibility and biomechanical studies have demonstrated that TLS is a safe and strong fixation methods for fusion beyond just the axial spine. However, not all spine segments have wide enough lamina to accept TLS. Preoperative computed tomography scan can help ensure the feasibility and safety of TLS insertion. Recent clinical reports have validated the application of TLS in subaxial spine, thoracic spine, hangman's fracture, and pediatric population. Conclusions: TLS can be used beyond axial spine; however, TLS insertion is only warranted when the lamina is thick enough to avoid further complications such as breakage. Preoperative computed tomography scans can be used to determine feasibility of such fixation construct.